Molecular cytogenetic identification of a novel wheat-Agropyron elongatum chromosome translocation line with powdery mildew resistance. - Xiaojun Li; Xiaoling Jiang; Xiangdong Chen; Jie Song; Cuicui Ren; Yajuan Xiao; Xiaohui Gao; Zhengang Ru (PLoS ONE)
Agropyron elongatum (Host.) Neviski (synonym, Thinopyrum ponticum Podp., 2n = 70) has been used extensively as a valuable source for wheat breeding. Numerous chromosome fragments containing valuable genes have been successfully translocated into wheat from A. elongatum. However, reports on the transfer of powdery mildew resistance from A. elongatum to wheat are rare. In this study, a novel wheat-A. elongatum translocation line, 11-20-1, developed and selected from the progenies of a sequential cross between wheat varieties (Lankaoaizaoba, Keyu 818 and BainongAK 58) and A. elongatum, was evaluated for disease resistance and characterized using molecular cytogenetic methods. Cytological observations indicated that 11-20-1 had 42 chromosomes and formed 21 bivalents at meiotic metaphase I. Genomic in situ hybridization analysis using whole genomic DNA from A. elongatum as a probe showed that the short arms of a pair of wheat chromosomes were replaced by a pair of A. elongatum chromosome arms. Fluorescence in situ hybridization, using wheat D chromosome specific sequence pAs1 as a probe, suggested that the replaced chromosome arms of 11-20-1 were 5DS. This was further confirmed by wheat SSR markers specific for 5DS. EST-SSR and EST-STS multiple loci markers confirmed that the introduced A. elongatum chromosome arms belonged to homoeologous group 5. Therefore, it was deduced that 11-20-1 was a wheat-A. elongatum T5DL∙5AgS translocation line. Both resistance observation and molecular marker analyses using two specific markers (BE443538 and CD452608) of A. elongatum in a F2 population from a cross between line 11-20-1 and a susceptible cultivar Yannong 19 verified that the A. elongatum chromosomes were responsible for the powdery mildew resistance. This work suggests that 11-20-1 likely contains a novel resistance gene against powdery mildew. We expect this line to be useful for the genetic improvement of wheat.